2001
DOI: 10.1117/12.438171
|View full text |Cite
|
Sign up to set email alerts
|

<title>Laser transmission through simulated cirrus clouds</title>

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, oatherina and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collectior of information, including suqqestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The zonal mean cloud radiative effect of shortwave peaks at 120 W•m −2 in the tropics and drops to −30 W m −2 , which means that multilayer clouds reflect less Sunlight than single-layer clouds. In another study [21], they found the global mean cloud radiative effects are −41.3 and −50.2 W m −2 . In 2019, M Wang et al [22] established the transmission model between the aircraft communication terminal and the UAV (Unmanned Aerial Vehicle) when the laser passed through the cirrus clouds, and analyzed the relative positions of the aircraft, UAV, and cirrus clouds, and the influence of different cirrus cloud physical properties on the laser transmission signal.…”
Section: Introductionmentioning
confidence: 93%
“…The zonal mean cloud radiative effect of shortwave peaks at 120 W•m −2 in the tropics and drops to −30 W m −2 , which means that multilayer clouds reflect less Sunlight than single-layer clouds. In another study [21], they found the global mean cloud radiative effects are −41.3 and −50.2 W m −2 . In 2019, M Wang et al [22] established the transmission model between the aircraft communication terminal and the UAV (Unmanned Aerial Vehicle) when the laser passed through the cirrus clouds, and analyzed the relative positions of the aircraft, UAV, and cirrus clouds, and the influence of different cirrus cloud physical properties on the laser transmission signal.…”
Section: Introductionmentioning
confidence: 93%